Lymphoedema management knowledge and practices among patients attending filariasis morbidity control clinics in Gampaha District, Sri Lanka - Chandrasena, TGA Nilmini (BioMed Central, 2004)
BACKGROUND: Little information is available on methods of treatment practiced by patients affected by filarial lymphoedema in Sri Lanka. The frequency and duration of acute dematolymphangioadenitis (ADLA) attacks in these patients remain unclear. This study reports the knowledge, practices and perceptions regarding lymphoedema management and the burden of ADLA attacks among patients with lymphoedema. METHODS: A semi-structured questionnaire was used to assess morbidity alleviation knowledge, practices and perceptions. The burden of ADLA attacks was assessed using one-year recall data. RESULTS: 66 patients (22 males, 44 females) with mean age 51.18 years (SD ± 13.9) were studied. Approximately two thirds of the patients were aware of the importance of skin and nail hygiene, limb elevation and use of footwear. Washing was practiced on a daily and twice daily basis by 40.9% and 48.5% respectively. However, limb elevation, exercise and use of footwear were practiced only by 21–42.4% (while seated and lying down), 6% and 34.8% respectively. The majority of patients considered regular intake of diethylcarbamazine citrate (DEC) important. Approximately two thirds (65.2%) had received health education from filariasis clinics. Among patients who sought private care (n = 48) the average cost of treatment for an ADLA attack was Rs. 737.91. Only 18.2% had feelings of isolation and reported community reactions ranging from sympathy to fear and ridicule. CONCLUSIONS: Filariasis morbidity control clinics play an essential role in the dissemination of morbidity control knowledge. Referral of lymphoedema patients to morbidity control clinics is recommended.